Yield, Productivity and Economics as Influenced by Different Fertility Levels and Genotypes in Single Cut Forage Sorghum under Rainfed Environment of the Northern Gujarat - Chongtham, S K; Jain, S K; Patel, P R (Annals of Arid Zone, 2018)
A field experiment was conducted at Sorghum Research Station, SDAU, Deesa during kharif season in 2016 with six single cut forage sorghum genotypes (SPH 1794, SPH 1797, SPV 2317, SPH 1752, CSH 13 and CSV 21F) grown at three fertility levels 75% recommended dose of fertilizer (RDF), 100% RDF (80 kg N + 40 kg P2O5 ha-1) and 125% RDF. Results showed that application of 100% RDF markedly increased yield attributes like plant height, stem diameter, green and dry fodder yields, fodder productivity and profit in single cut forage sorghum. Genotypes SPH 1794, SPH 1797, SPV 2317 and SPH 1752 were promising as single cut forage sorghum under rain-fed environment of Northern Gujarat as they performed well in terms of growth, yields and productivity with higher remuneration than other genotypes. Key words: Fertility levels, forage sorghum, genotypes, yield, north Gujarat.